(untitled) (diségno, 2022)
The book Captura fotográfica gigapíxel de obras de arte by Pedro Cabezos Bernal, Pablo Rodríguez Navarro, Teresa Gil Piqueras, Juan Cisneros Vivó, and Cristian Gil Gil, published in 2022 and edited by edUPV, deals with the acquisition and processing of highly informative photographic images, called precisely gigapixels. This is an innovative technique that is gaining popularity in several international museums as a means of documenting, analyzing, and disseminating pictorial artistic heritage through very high resolution photographs. [read more]